(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Complex umbilical cord entanglement occurs less frequently and is associated with an increased risk of adverse perinatal outcomes. It is associated with umbilical artery pH and base excess levels that are significantly unfavorable, higher incidence of nonreassuring fetal heart rate, meconium-stained amniotic fluid, neonatal intensive care unit admissions, emergency cesarean section, and stillbirth. Case presentation: A 44-year-old para 2+0 gravida 3, with 2 previous cesarean delivery scars at 35 weeks presented with a history of reduced fetal movements for 24 hours. She had attended two antenatal care visits. Her blood group was A, rhesus negative, with hemoglobin levels of 11.2 g/dl, and normal platelets. Urinalysis and serology for HIV, hepatitis B, and Venereal Disease Research Laboratory test were nonreactive. She had received anti-D prophylaxis after her previous deliveries. An urgent obstetric ultrasound scan showed features consistent with intrauterine fetal death. Her coagulation profile was within the normal range. She was admitted for hysterotomy. Intraoperatively, a fresh stillborn baby boy was extracted with a cord around the neck tightly twice and entangled around the trunk. Conclusion: Complex umbilical cord entanglement occurs less frequently and associated with an increased risk of adverse perinatal outcomes. The risk of adverse perinatal outcomes increases with ≥3 loops of the umbilical cord. It is important to look out for cord entanglement antenatally by ultrasonography, particularly when assessing cases of decreased fetal movements.